Alcohol Effects on Cardiac Function. Issue 2 (16th March 2015) - Gardner, Jason D.; Mouton, Alan J.
ABSTRACT: The consumption of ethanol can have both beneficial and detrimental effects on the function of the heart and cardiovascular system, depending on the amount consumed. Low‐to‐moderate amounts of ethanol intake are associated with improvements in cardiac function and vascular health. On the other hand, ethanol chronically consumed in large amounts acts as a toxin to the heart and vasculature. The cardiac injury produced by chronic alcohol abuse can progress to heart failure and eventual death. Furthermore, alcohol abuse may exacerbate preexisting heart conditions, such as hypertension and cardiomyopathy. This article focuses on the molecular mechanisms and pathophysiology of both the beneficial and detrimental cardiac effects of alcohol. © 2015 American Physiological Society. Compr Physiol 5:791‐802, 2015.